IMPLEMENTASI KEGIATAN MELUKIS BERBASIS TEMA CERITA TERHADAP KEMAMPUAN BAHASA ANAK USIA 5 – 6 TAHUN DI TKIT ANAKKU SETU - ardiani, khofifah; Roza Yenita; Wantini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study shows that the implementation of story-based painting activities at TKIT ANAKKU Setu is effective in improving the language skills of children aged 5–6 years. Interaction during the activities was good, and the children were very enthusiastic and actively participated. Through creative painting activities and storytelling, children can develop speaking and listening skills, enrich their vocabulary, and be able to describe their paintings verbally. Thus, story-based painting activities play an important role in supporting children's overall language development.